Role of eslicarbazepine in the treatment of epilepsy in adult patients with partial-onset seizures - Martin E Brown; Rif S El-Mallakh (Dove Medical Press, 2010)
Martin E Brown, Rif S El-Mallakh1Department of Neurology, 2Department of Psychiatry and Behavioral Sciences, University of Louisville School of Medicine, Louisville, Kentucky, USAAbstract: Eslicarbazepine is a new dibenzazepine antiepileptic agent. It is a high affinity antagonist of the voltage-gated sodium channel. It is closely related to both carbamazepine and oxcarbazepine. Eslicarbazepine has similar affinity to inactivated sodium channels (channels in just activated neurons) as carbamazepine, and greater efficacy in animal models of seizure than oxcarbazepine. In human placebo-controlled trials of a single daily dose of eslicarbazepine added to other anti-epileptic agents, significant seizure reductions occurred with 800 and 1200 mg daily, with nearly half of the patients experiencing a greater than 50% reduction in seizure frequency. Adverse events (AEs) occurred in over 50% of patients receiving therapeutic doses of eslicarbazepine (compared to 31.4%–44.7% of placebo-treated subjects), but were generally mild or moderate. Eight to 19.6% of eslicarbazepine treated patients discontinued due to AEs (compared to 3.9%–8.5% of placebo-treated subjects). In these patients receiving combination anticonvulsant therapy, the most common AEs were dizziness, nausea and vomiting, somnolence, and diplopia. Eslicarbazepine is an effective and reasonably well-tolerated adjunct in patients with suboptimal control of their partial seizures.Keywords: eslicarbazepine, licarbazepine, voltage-gated sodium channel, partial-onset seizures, epilepsy